Verba Emosi Marah Dalam Bahasa Aceh: Kajian Metabahasa Semantik Alami - Khaira, Cut Nuswatul; Mulyadi, Mulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to look at the representation of reality in language, especially in the context of using words to express emotions, focusing on the word "angry" in the Acehnese language. Natural Semantic Metalanguage Theory (MSA) is used as a theoretical framework to analyze the meaning of these words. The research method used is qualitative descriptive with data collection through interviews, textbooks, and videos in Acehnese. The results of the analysis show that the words used to express angry emotions in Acehnese, such as "bingeing", "cat", "dam", "tune", "as a", "chicken", and "lust", have basic meanings—the same but different in the context and intensity of emotional expression. The meaning component analysis highlights differences in the experience and expression of angry emotions and strengthens understanding of the variation and complexity of human emotions in specific cultural contexts. This research provides a deeper understanding of the role of language in representing emotional reality and enriches the study of emotional semantics in the Acehnese cultural context.